2015
DOI: 10.1177/0013164414565006
|View full text |Cite
|
Sign up to set email alerts
|

Does Matching Quality Matter in Mode Comparison Studies?

Abstract: This article provides a brief overview and comparison of three matching approaches in forming comparable groups for a study comparing test administration modes (i.e., computer-based tests [CBT] and paper-and-pencil tests [PPT]): (a) a propensity score matching approach proposed in this article, (b) the propensity score matching approach used by Lottridge, Nicewander, and Mitzel, and (c) a modified approach of matched samples comparability analyses (MSCA) mentioned by Way, Davis, and Fitzpatrick. Different matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Results from six studies favored paper testing in the following areas of language arts: 9th‐grade English (Kim & Huynh, 2010; Lottridge et al., 2011), reading comprehension (Jerrim, 2016; Kim & Kim, 2013; Mangen et al., 2013), and English language arts/literacy (Liu et al., 2016). Only one study indicated comparability on English language proficiency tests in some analyses for students in grades 9–12 (Zeng et al., 2015). In studies of high school mathematics subjects such as algebra and geometry, four studies had results that favored paper testing (Jerrim, 2016; Liu et al., 2016; Lottridge et al., 2011; Minnesota Department of Education, 2016) and two indicated comparability (Liu et al., 2016; Moon, 2013).…”
Section: Prior Researchmentioning
confidence: 99%
“…Results from six studies favored paper testing in the following areas of language arts: 9th‐grade English (Kim & Huynh, 2010; Lottridge et al., 2011), reading comprehension (Jerrim, 2016; Kim & Kim, 2013; Mangen et al., 2013), and English language arts/literacy (Liu et al., 2016). Only one study indicated comparability on English language proficiency tests in some analyses for students in grades 9–12 (Zeng et al., 2015). In studies of high school mathematics subjects such as algebra and geometry, four studies had results that favored paper testing (Jerrim, 2016; Liu et al., 2016; Lottridge et al., 2011; Minnesota Department of Education, 2016) and two indicated comparability (Liu et al., 2016; Moon, 2013).…”
Section: Prior Researchmentioning
confidence: 99%
“…For example, if test forms were available in paper and computer-based versions, one may compare the means for paper and computer-based tests to see if they were comparable. Many score comparability studies of this type exist (see Wang et al, 2007Wang et al, , 2008Zeng et al, 2015). In the context of evaluating score comparability of alternate CAT forms, comparing observed score distributions or moments of these distributions is challenging because few examinees typically take each form and performance on alternate forms is expected to differ as a function of ability.…”
mentioning
confidence: 99%